The Influence of Family and Peer Support on Healthy Lifestyles on Adolescents in Medan City - Ghina Atikah; Kintoko Rochadi; Zulhaida Lubis (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Basic Health Research (Riskesdas) in 2018 recorded that 2.5 percent of stroke sufferers had suffered from stroke since the age of 18-24 years and 13.22 percent suffered from hypertension. In addition, non-communicable diseases found in school-age children and adolescents were cancer at 0.47 percent, asthma at 2.2 percent, diabetes mellitus at 1.6 percent, heart disease at 0.7 percent and obesity at 10 percent. Unhealthy lifestyles are the cause of non-communicable diseases in adolescents. The purpose of this study was to determine the relationship between family and peer support and a healthy lifestyle in adolescents in Medan City in 2024. This type of research is a quantitative research that is an analytical survey with a cross-sectional method. This research was conducted from February to July 2024. The study population was high school adolescents in Medan City who were selected as sample clusters in this study, namely 7679 people. The research sample was 334 respondents using the Isaac and Michael formula with the proportional random sampling method for each school. The data collection method used a questionnaire through a questionnaire. Data analysis using univariate and bivariate analysis using the Chi Square test, the results of which are described in the frequency distribution table. The results showed that the lifestyle of adolescents in Medan City was in the unhealthy lifestyle category with a percentage of 61.7 percent. There is a relationship between family and peer support and a healthy lifestyle in adolescents in Medan City. all variables obtained values (p <0.05). So it can be concluded that there is a relationship between family and peer support and a healthy lifestyle in adolescents in Medan City. Keyword: Adolescents, Family Support, Healthy Lifestyle, Peer